EFFECT OF IRONWOOD BARK EXTRACT GEL ON LYMPHOCYTE COUNT IN BUCCAL MUCOSA WOUND HEALING RATS - Mahmud Muhlisin; I Wayan Arya Krishnawan Firdaus; Maharani Lailyza Apriasari; Juliyatin Putri Utami; Erida Wydiamala (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Wounds are disruptions caused by chemical or physical trauma, resulting in tissue damage. During the healing process of oral mucosal wounds, the body initiates defensive and protective immune responses against injury. The acute inflammatory phase is the initial stage of wound healing, marked by the body’s response to injury within a few hours. Lymphocyte cells play a crucial role in the inflammatory phase as part of the adaptive immune system in wound healing. Secondary metabolites in the ironwood bark extract gel, such as proanthocyanidins, phenolics, and flavonoids, function as immunomodulators to enhance immune activity and act as anti-inflammatory and antioxidant agents to accelerate wound healing. Purpose: To prove the effect of ironwood bark extract gel at concentrations 5%, 12.5%, and 20% on lymphocyte cell number in the buccal mucosa incision wounds of male Wistar rats on days 3, 5, and 7. Methods: This study employed a pure experimental design with a post-test only with a control group design, using 36 male Wistar rats divided into treatment and negative control groups. Results: Two-way ANOVA tests revealed significant effects based on treatment and observation days (p < 0.05). Conclusion: Ironwood bark extract gel at concentrations of 5%, 12.5%, and 20% increased lymphocyte cell number on day 3, peaked on day 5 and decreased on day 7 compared to the control group (gel base). Keywords: eusideroxylon zwageri gel, lymphocyte cells, oral mucosal wound healing,